A qualitative examination of the role of school leadership teams in secondary school mental health policy and practice for autistic students - Cetintas, Seyda; Van Herwegen, Jo; Al-Jayoosi, Heba; McEvoy, Roisin; Hurry, Jane; Pavlopoulou, Georgia (Frontiers in Education, 2026)
BackgroundAlthough school-based mental health initiatives are gaining attention, research remains limited on effective and sustainable implementation, especially for autistic students. School leadership play a pivotal role in shaping mental health initiatives. However, their roles and perspectives, particularly regarding autistic students, are under-researched.MethodsWe applied Reflexive Thematic Analysis to 22 semi-structured interviews with senior leadership teams’ (SLTs) members from state-funded mainstream secondary schools across six regions in England. Interviews were co-produced with an advisory team and adopted a curious stance to explore SLT members’ perspectives on promoting and supporting autistic students’ mental health.ResultsUsing inductive coding and iterative discussions, we identified four key themes: (1) SLTs’ views and beliefs about autism and autistic students, (2) The use of one-size-fits-all approaches in mental health policy and provision, (3) The difficulty of overcoming and deepening systemic barriers in organizing mental health provision, and (4) The need to deepen participation with stakeholders and services. Findings revealed existing gaps and barriers in autism-informed provision and highlighted the changes and resources needed to facilitate mental health provision for autistic students from SLTs’ perspectives.ConclusionResults offer actionable insights for practice and policy, especially in light of the systemic and cultural challenges SLTs face.